Green Training and Development Practices on Environmental Sustainability: Evidence from Wamco PLC - Tinuke Moradeke Fapohunda; Kabiru Ishola Genty; Lateef Okikiola Olanipekun (Universitas Brawijaya, 2022)
Green training and development practices have been acknowledged as veritable tools for addressing environmental challenges; it is also a key ingredient for promoting the acceptance of environmental conservation in the workplace because in the long run, it helps to creating a win-win situation for both management and employees. To this end, this study examined effect of green training and development practices on environmental sustainability with the objective of examining the effect of developing green abilities on environmental awareness; and examining the relationship between green knowledge and employees commitment towards the environment. Data was collected through the quantitative means from 175 employees of WAMCO Nigeria plc. 5Findings revealed that developing green abilities accounts for only 93.7% of variations in environmental awareness. This implies that developing green abilities have positive significant effect on environmental awareness as an indicator of environmental sustainability; in the same vein, there exists a positive and significant relationship between Green Knowledge and Employee Commitment towards the Environment which is a component of Environmental Sustainability with (r=0.942, p-value<0.05). The study concluded that green training and development practices are veritable tools for promoting employees consciousness towards the overall achievement of sustainable development goals. Thus, employee engagement and involvement in green activities should be prioritised and strengthened through periodic training and development centered on the attainment of green goals.